Agricultural and Ecosystem Services: A Case Study of Asparagus in Ica, Peru - Gómez, Rosario (2015)
Sustainable agriculture is growing around the world and is synonymous with increases in crop productivity based on the efficient use of natural resources and employing an ecosystem and intertemporal approach. This study explores the link between agriculture and ecosystem services on the basis of a case study of the asparagus crop in Ica. It emphasizes the manner in which natural capital supports the development of this crop as well as the capacity of producers to adopt soil conservation and water management practices. The results show that the probability of adopting any such practices increases with levels of education, use of extension services, capacity building, and access to credit.